Stereoselective Syntheses of 3′-Hydroxyamino- and 3′-Methoxyamino-2′,3′-Dideoxynucleosides - Bose, Sritama (Org Lett, 2019)
[Image: see text] Aminonucleosides are used as key motifs in medicinal and bioconjugate chemistry; however, existing strategies toward 3′-hypernucleophilic amine systems do not readily deliver deoxyribo-configured products. We report diastereoselective syntheses of deoxyribo- and deoxyxylo-configured 3′-hydroxyamino- and 3′-methoxyamino-nucelosides from 3′-imine intermediates. The presence or absence of the 5′-hydroxyl-group protection dictates facial selectivity via inter- or intramolecular delivery of hydride from BH(3) (borane). Protecting group screening gave one access to previously unknown 3′-methoxyamino-deoxyguanosine derivatives.